Assessing Genotype by Environment Interaction in a Diverse Barley Panel for Enhanced Breeding Strategies in Morocco - Moulakat, Adil; Kehel, Zakaria; Bouhlal, Outmane; Ibriz, Mohammed; Sanchez-Garcia, Miguel (2024)
Barley (Hordeum vulgare) is an important cereal crop cultivated over a wide range of environments and in diverse agro-ecologies in Morocco. Genotype by environment interaction (GxE) has important consequences in barley breeding. It complicates testing and selection of superior genotypes and reduces genetic progress in breeding programs. The use of a diversity panel is an important component in a breeding program to understand GxE, traits linkage and feed crossing-blocks with the necessary diversity.